The aesthetic field - Fraser, Andrea 1965-; Kusch, Martin 1964- (Andrea Fraser and Galerie Metropol, 1993)
"Edited from videotapes of an artists's lecture series of the same name held in 1992 at the Hochshule für Angewandte Kunst, Vienna, The aesthetic field distills eleven artistic positions in five-minute clips that, together, demonstrate the differing and often contradictory ways in which artists define their practices and attempt to address their audiences. Artists included: Peter Weibel, Jeff Koons, Peter Fend, Colin de Land, Jessica Stockholder, Gerwald Rockenschaub, John Miller, Raymond Pettibon, Christian Philipp Müller, Renee Green and Andrea Fraser"
Title from disc
"Edited from videotapes of an artist's lecture series of the same name held in 1992 at the Hochschule für Angewandte Kunst, Vienna, The Aesthetic Field distills eleven artistic positions in five-minute clips that, together, demonstrate the differing and often contradictory ways in which artists define their practices and attempt to address their audiences. Artists included: Peter Weibel, Jeff Koons, Peter Fend, Colin de Land, Jessica Stockholder, Gerwald Rockenschaub, John Miller, Raymond Pettibon, Christian Philipp Müller, Renee Green and Andrea Fraser."
Keywords: Artists; Aesthetics; Film; DVD-Video